Student Involvement in Curriculum Development Enhances Medical Education - Jacline Griffeth; Alexandra Sawyer; Nolan Johnson; Osama Hashmi; Neha Gupta; Sarah Swartz; Kathryn Martin; Carol Nichols (Georgia Southern University, 2017)
Background: During the 2014 annual review of the curriculum for first year medical students at the Medical College of Georgia, the public health module was noted as an area that needed improvement. To address this concern, a Public Health Curriculum Workgroup was formed for the purpose of identifying specific areas to improve and developing a more robust and integrative curriculum. A small cohort of medical students with public health backgrounds were invited to be members of this workgroup and participate in the development and delivery of public health content to the next cohort of first year medical students. We hypothesized that having this type of student participation results in a more clinically relevant and engaging curriculum. Methods: The curriculum workgroup met weekly to establish learning objectives, prioritize topics, and design interactive activities. The student members contributed to both curricular planning and content delivery. First year medical students completed course evaluations following the public health curriculum. These evaluations included five Likert scale questions and three narrative feedback response questions. Evaluation data before and after student involvement in the curriculum was examined. Results: Student evaluations of the overall quality of the public health curriculum increased 38% from 2014-2016. The measure of how well the content contributed to development as a future physician increased 36%. There was a 33% increase in how well the instructional materials aided understanding of topics. Theming of narrative evaluation comments showed that student involvement in the curriculum was well received. In 2016, 28.4% of narrative comments cited student presentations as the most valuable aspect of their public health experience. Conclusions: Involving medical students with public health backgrounds in curriculum development and content delivery of a public health module for first year medical students led to improvements in overall quality, clinical relevance, and instructional materials. Key words: public health, curriculum development, student involvement, evaluation